Levels of Circulating TIMP-2 and MMP2-TIMP2 Complex Are Decreased in Squamous Cervical Carcinoma - Talvensaari-Mattila Anne; Turpeenniemi-Hujanen Taina (Obstetrics and Gynecology International)
Background. The role of matrix metalloproteinase-2 and -9 (MMP-2, MMP-9) in matrix degradation and metastasis has been described in various tumors. Their action is inhibited by their natural tissue inhibitor molecules TIMP-1 and -2. Methods. The study population consisted of 12 squamous cervical carcinoma patients and 27 healthy volunteer control patients. MMP-9, MMP-2-TIMP-2 complex, TIMP-1, and TIMP-2 were analyzed from serum samples using enzyme-linked immunoassay (ELISA). Results. The mean levels of serum TIMP-2 and of MMP-2-TIMP-2 complex were higher in healthy controls compared to patients with a malignant tumor. Serum TIMP-2 values decreased significantly from healthy controls (median 323 𝜇g/l, range 305–342 𝜇g/l) to malignant (median 136 𝜇g/l, range 120–151 𝜇g/l) squamous cervical carcinoma patients (𝑃<.000). Also, serum proMMP2-TIMP2 complex values decreased from control patients to squamous cervical carcinoma patients (𝑃<.006). Conclusion. This paper shows that the levels of circulating TIMP-2 and that of MMP-2-TIMP-2 complex are lower in squamous cervical carcinoma patients than in healthy women.